Perancangan Program Aplikasi Appointment pada Labrows Berbasis Website - Florentina Martha; Ery Dewayani; Zyad Rusdi (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
The purpose of writing this thesis is to build an appointment systems at Labrows based on website. This program makes customer easier in scheduling and managing appointments at Labrows. In the absence of such information systems make more difficult customers to research and product maintenance services desired. Using methods of SDLC (System Develompment Life Cycle) is a development life cycle is expected to result in a more perfect system because it allows a re-evaluation of the system development process due to the rotation of the system as well as web development, information system was developed using PHP, HTML, and MySql. On testing the system information is based on using the black box. Conclusions and suggestions that there is need for dissemination of research information service system of registration, appointment reservation, ordering and other products need to be done by Labrows to customers, may be developed and utilized properly and can be used by Labrows, to simplify and speed service to customers